2009
DOI: 10.1044/1092-4388(2008/07-0219)
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Temporal Gap Identification on Speech Perception by Users of Cochlear Implants

Abstract: Purpose This study examined the ability of listeners using cochlear implants (CIs) and listeners with normal-hearing (NH) to identify silent gaps of different duration, and the relation of this ability to speech understanding in CI users. Method Sixteen NH adults and eleven postlingually deafened adults with CIs identified synthetic vowel-like stimuli that were either continuous or contained an intervening silent gap ranging from 15 to 90 ms. Cumulative d’, an index of discriminability, was calculated for ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 33 publications
0
26
0
Order By: Relevance
“…A number of studies have shown relationships between perceptual temporal processing and speech perception (e.g., Fu, 2002; Luo et al, 2008; Sagi et al, 2009). If temporal inputs from the auditory nerve are the basis for perceptual temporal processing, then the results from the present study may have implications for changes to future speech-processing strategies.…”
Section: Resultsmentioning
confidence: 99%
“…A number of studies have shown relationships between perceptual temporal processing and speech perception (e.g., Fu, 2002; Luo et al, 2008; Sagi et al, 2009). If temporal inputs from the auditory nerve are the basis for perceptual temporal processing, then the results from the present study may have implications for changes to future speech-processing strategies.…”
Section: Resultsmentioning
confidence: 99%
“…If the mechanisms underlying improvement of GDTs as a function of level are related to loudness percepts, then examining the latter might improve temporal gap detection in CI users. There is a growing body of evidence suggesting a relation between GDTs and speech recognition (Muchnik et al, 1994; Sagi et al, 2009). Hence, the extent to which CI recipients are able to resolve temporal information, including their ability to detect a silent gap, should be maximized with the expectation that their speech performance would also improve.…”
Section: Discussionmentioning
confidence: 99%
“…Although channel vocoding preserves the amplitude difference between primary-and secondary-stressed target words, listeners did not use this cue to lexical stress in the vocoder condition. There are several possible explanations for this result: (1) the small difference in amplitude may not be sufficient to help in distinguishing primary and secondary stress, (2) amplitude is not a reliable cue to the degree of lexical stress (e.g., Beckman, 1986;Fear et al, 1995;Mattys, 2000;Sluijter and Van Heuven, 1996) and seems to be a less important cue for lexical stress in English (e.g., Chrabaszcz et al, 2014;Fry, 1955Fry, , 1958Lehiste, 1970;Mattys, 2000), and/or (3) listeners' ability to perceive slight temporal and intensity changes in the spectrally degraded signal is reduced, as suggested by previous vocoder and CI studies (Oxenham and Kreft, 2014;Rogers et al, 2006;Sagi et al, 2009;Won et al, 2011).…”
Section: Discussionmentioning
confidence: 88%